An Exploratory Study on the Role of Burnout and Devaluation among Staff in Psychiatric Correctional Facilities - Olson, Lindamarie (International journal of offender therapy and comparative criminology, 2022)
Correctional staff work in demanding job environments that can lead to increased burnout. Research aims were to determine the prevalence of burnout and devaluation of consumers (i.e., individuals in their care) and their families among correctional staff, examine associations between burnout and devaluation of consumers and their families, and determine significant predictors of burnout. This exploratory study investigated 30 correctional staff in a specialized psychiatric correctional facility for individuals with mental illness in Mexico City. Correctional staff experienced low to moderate burnout, reported high levels of devaluation of consumers (DCS), and low levels of devaluation of consumers’ families (DCFS). The implications of burnout on DCS and DCFS warrant large scale research and should compare burnout and devaluation in specialized psychiatric correctional facilities versus general correctional facilities.